The effects of a Iron/GleptoForte in anemic susceptible piglets - Crane, Courtney; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
New born piglets are typically born with an iron deficiency due to a variety of reasons, creating an importance for iron supplementation for the piglets. A 200-mg injection of iron is used and has been previously used to improve growth rate and iron levels in piglets. Gelptoforte (Ceva Animal Health, LCC., Lenexa, KS) is an injectable iron that contains gleptoferron and is used to prevent piglets from becoming anemic. In a 21-d study 336 newborn pigs (DNA 241 x 600), were used to evaluate the effects of Gelptoforte based on performance and blood iron levels. A total of 28 litters were used with an equal number of pigs per sow. Using a randomized design treatment, treatments were split among 56 piglets per treatment; negative control consists of receiving no iron injection and increasing levels of Gelptoforte to 50, 100, 150, 200, or 200 mg plus a 100-mg booster at d 11 of farrowing. 1ml of Gelptoforte contained 200mg of iron. Measured from blood samples were Hemoglobin (Hgb), Hematocrit (Hct), Serum Fe, and Total Iron Binding Capacity (TIBC). With increasing Gelptoforte ADG and BW of the piglets increased (quadratic; P=0.018). There was no evidence of difference in the three periods between the 200 mg and 200 mg + 100 mg injection of Gelptoforte showing no difference in the booster shots of 200 mg given at d 3 and boosters given at d 11. There was no difference n observed hematological criteria measured on d 3 prior to iron injection. For Hgb, (P = 0.001) observed with Hgb increasing (quadratic; P= 0.001) on d 11 and 21 with the 0-mg treatment having the lowest and the 200-mg treatment having the highest Hgb values. On d 21, a difference (P= 0.046) was observed between 200 mg and 200 mg + 100 mg, with the 200 mg + 100 mg having a higher Hct value. For Serum Fe (P=0.001) was observed which serum Fe increased (P=0.001) on d 11 and increased (quadratic; P= 0.001) on d 21 with 0 mg treatment with lowest value and 200 mg having highest value. Also, d 21 showed a significant increase for 200 mg with booster of 100mg. In summary, a negative control of iron injection resulted in the poorest growth and blood parameters of iron status of suckling piglets as expected. However, the injection of 100 mg of Gleptoforte resulted in the greatest growth rate and the injection of 200 mg + 100 mg of Gleptoforte concluded to improving hematological criteria but did not influence piglets’ growth rate compared to 200 mg alone. Overall the 200-mg injection of Gelptoferote has the best results for use outside of this experiment.
Keywords: Fall 2017